Peripheral neuropathy associated with levodopa–carbidopa intestinal infusion: a long‐term prospective assessment. (25th October 2015) - Merola, A.; Romagnolo, A.; Zibetti, M.; Bernardini, A.; Cocito, D.; Lopiano, L.
Abstract : Background and purpose: Subacute and chronic peripheral neuropathies (PNP) have been reported in Parkinson's disease (PD) patients treated with levodopa/carbidopa intestinal gel infusion (LCIG), although several aspects of their incidence and pathogenesis still remain to be clarified. This study main objective is to prospectively report the 2‐year incidence of PNP in patients treated with LCIG. Methods and results: The clinical, hematological, nutritional and electrophysiological assessments of 33 consecutive patients have been prospectively collected and evaluated. At baseline (before the start of LCIG therapy), 3/33 (9%) patients showed symptomatic PNP and 7/33 (21%) subclinical PNP. During a follow‐up of 24.36 ± 12.18 months, 2/23 patients with normal baseline clinical‐electrophysiological assessment developed a subacute PNP, 2/23 developed a chronic PNP and 7/23 developed a subclinical PNP. LCIG was immediately halted in the subacute cases, while the infusion therapy was not interrupted in chronic and subclinical forms. All PNP were supplemented with vitamin B1 and B12, showing a clinical improvement and/or substantial stability at the following evaluations. Higher levodopa‐equivalent daily dose ( P : 0.024) and homocysteine levels ( P : 0.041) were found in chronic PNP, while no correlations were observed with vitamin B12, folate and UPDRS values. A trend towards BMI reduction was observed in both PNP and unaffected subjects and one patient developed a symptomatic PNP associated with a relevant weight loss. Conclusions: Serial clinical‐electrophysiological evaluations are mandatory in patients treated with LCIG, given the possible risk of subacute and chronic PNP. No clear causative factors has been recognized in the subacute forms, whilst homocysteine‐mediated neurotoxicity seems to underlie the pathogenesis of chronic forms. Abstract : Clickhere to view the accompanying paper in this issue.